Securing microservice APIs : sustainable and scalable access control - McLarty, Matt; Wilson, Rob; Morrison, Scott (O'Reilly Media, 2018)
There are several techniques for controlling access to web APIs in microservice architectures, ranging from network controls to cryptographic methods and platform-based capabilities. This short ebook introduces an API access control model that you can implement on a single platform or across multiple platforms to provide cohesive security across your network of microservices. Until now, speed of delivery rather than security has motivated organizations to adopt a microservices architecture. Authors Matt McLarty and Rob Wilson propose a vocabulary and model for logical and physical systems of microservices, review current practices for web API access control in a microservice architecture, and present DHARMA--a comprehensive, platform independent approach to API access control. This ebook is ideal for architects, product owners, development leaders, platform teams, and operational managers. This ebook includes: A platform-neutral overview of the microservices landscape Current network-, trust-, and platform-based security technologies and solutions that apply to microservice APIs The proposed DHARMA cross-platform model for securing microservice API access control A word on the future direction of microservice API security.